Exfoliation-restacking synthesis of coal-layered double hydroxide nanosheets/reduced graphene oxide composite for high performance supercapacitors. (10th January 2015) - Huang, Zongchuan; Wang, Senlin; Wang, Jianpeng; Yu, Yaming; Wen, Jingjing; Li, Rui
Graphical abstract: Abstract: CoAl-layered double hydroxide nanosheets/reduced graphene oxide composite (CAN-LDH-NS/rGO) was fabricated by an exfoliation-restacking process, during which, the nitrate-intercalated CoAl-layered double hydroxide nanosheets (CAN-LDH-NS) were restacking on the surface of the reduced graphene oxide (rGO) flakes by means of electrostatic interactions. Electrochemical performances of the composite were enhanced due to the incorporation of CAN-LDH-NS and rGO flakes. The specific capacitance of the composite was found to be about 1296 F g −1 at a current density of 1 A g −1 . Furthermore, the capacitance of the composite maintained 90.5% of the initial capacitance even at a high current density of 15 A g −1 after 1000 cycles. These results indicate that the CAN-LDH-NS/rGO composite is a promising material for supercapacitors. Our presented work not only provides a facile preparation approach to LDH/rGO hybrid materials, but also sheds a new light on electrode design for supercapacitors.